Music, music therapy and trauma : international perspectives - Sutton, Julie P., 1956- (J. Kingsley Publishers, 2002)
Music communicates where words fail, and music therapy has been proven to connect with those who were thought to be unreachable, making it an ideal medium for working with those who have suffered psychological trauma. Music, Music Therapy and Trauma addresses the need for an exploration of current thinking on music and trauma. With chapters written by many of today's leading specialists in this area, music and trauma is approached from a wide range of perspectives, with contributions on: neurology of trauma and music; music and trauma in general; social and cultural perspectives on trauma; con.